KOMUNIKASI MATEMATIK DALAM PEMBELAJARAN PROGRAM LINIER BERKARAKTERISTIK KEWIRAUSAHAAN UNTUK MENUMBUHKAN JIWA WIRAUSAHA MAHASISWA PENDIDIKAN MATEMATIKA - Retno Marsitin (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2015)
This study aims to describe the implementation of mathematical communication skills in teaching linear program with entrepreneurial characteristic to foster the entrepreneurial spirit in students of mathematics education. This study used a qualitative approach, with a type of research is classroom action research, which was conducted in two cycles. Subject of this research is students of mathematics education who take a course in linear program with the total of 25 students. Data were collected through observation, testing, documentation, and field notes. Data were analyzed from early action learning and reflection made up statements. Data analysis techniques used in this research is descriptive qualitative data analysis that includes data reduction, data presentation, analyzing data and drawing conclusions (verification). The validity of the data use triangulation techniques. The results showed that an improvement in mathematical communication skills and foster an entrepreneurial spirit of student in the learning of linear program. This is showed by the data obtained on students’ academic ability success of 76%, the ability of mathematical communications with achievement of 82, 33% and students’ entrepreneurial spirit achieved 79, 67%.